Methodology for Combating Extremism in Cyberspace: Experience of the Shanghai Cooperation Organization - V. P. Kirilenko; A. D. Khlutkov; G. V. Alekseev (Евразийская интеграция: экономика, право, политика)
The  studies of extremist discourse in cyberspace use set scientific methods to protect traditional spiritual values, such as state sovereignty, human rights and freedoms, historical and cultural heritage. The experience of the member States of the Shanghai Cooperation Organization (SCO) on the implementation of regional international agreements aimed at combating extremism should be applied in the organization of countering extremist crimes committed using digital technologies.Aim . To characterize approaches to combating extremism in cyberspace within the SCO and to determine the methodology for assessing the degree of public danger of manifestations of extremism.Methods. The study on extremism in SCO apply a  comparative legal  method when posing the problem of criminalization of extremist practices and use discourse analysis of the extremism in cyberspace problem for assessing the public danger of radical ideology.Results. Three groups of methods are used in the fight against extremism: methods of legal regulation, methods of studying and assessing the public danger of extremist materials and methods of scientific research of extremism. Prohibitive legal regulation in cyberspace is applied to media content that, according to the conclusion of linguistic expertise, contains signs of extremist materials. The doctrinal basis for the legal assessment of the linguistic expertise of extremist materials is the socio-legal research conducted in the SCO member states.Conclusions. The propaganda of extremism in cyberspace qualifies as an abuse of freedom of speech, since extremist ideology leads to terrorism. The SCO consensus on the need to combat extremism is based on a  scientific methods  system for radical ideology research, among which discourse analysis and narrative dialogue research will play an increasing role with the digital transformation.